Sustainable Porous Carbon with High Specific Surface Area from Soybean Shell via Hydrothermal Carbonization with H3PO4 for Electric Double‐Layer Capacitor Applications. Issue 3 (19th December 2019) - Wu, Yan; Cao, Jing-Pei; Zhao, Xiao-Yan; Zhuang, Qi-Qi; Zhou, Zhi; Zhao, Ming; Cui, Xin; Zhao, Yun-Peng; Wei, Xian-Yong
Abstract : Soybean shell (SS), as the byproduct of soybeans, is converted into porous carbon (PC) with a high specific surface area (SSA) via hydrothermal carbonization with H3 PO4 followed by KOH activation. No obvious effect on the crystal structure of PC can be found by addition of H3 PO4 during the hydrothermal process. However, the SSA of PC increases remarkably compared with hydrothermal carbonization without H3 PO4, as H3 PO4 assists in hydrothermal carbonization dehydration reactions and creates some pores beneficial for KOH activation. The SSA of the obtained PC reaches 2523 m 2  g −1, and the hierarchical pore structure is mainly in 0.6–50 nm. The sample prepared by hydrothermal carbonization with 10 wt% H3 PO4 and activation by KOH with the ratio of KOH/10‐hydrochar 3 under 700 °C exhibits a specific capacitance of 301 F g −1  in 6 m KOH electrolyte at the current density of 0.1 A g −1 . It also has an excellent cycling stability with the specific capacitance remaining at 93.8% after 15 000 cycles. Furthermore, the energy density is 8.1 Wh kg −1  in the two‐electrode system. These results display that PC based on SS is a promising electrode material for the electric double‐layer capacitor. Abstract : Soybean shell, as the byproduct of soybeans, is converted into porous carbon (PC) with a high specific surface area via hydrothermal carbonization with H3 PO4 followed by KOH activation. PC as the electrode for an electric double‐layer capacitor shows good electrochemical performance and an excellent cycling stability in a two‐electrode system in 6 m KOH electrolyte.